2021
DOI: 10.1210/clinem/dgab602
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Kiss1 Neurons With Kappa Opioid Receptor Agonists to Treat Polycystic Ovary Syndrome and Vasomotor Symptoms

Abstract: Context Recent evidence suggests that vasomotor symptoms (VMS) or hot flashes in the postmenopausal reproductive state and polycystic ovary syndrome (PCOS) in the premenopausal reproductive state emanate from the hyperactivity of Kiss1 neurons in the hypothalamic infundibular/arcuate nucleus (KNDy neurons). Objective We demonstrate in 2 murine models simulating menopause and PCOS that a peripherally-restricted kappa receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 93 publications
0
13
0
Order By: Relevance
“…95 In this study, inhibition of kisspeptin neuronal activity by chronic administration of kappa opioid receptor agonists to bilaterally ovariectomised mice with experimentally induced hyperactivity of KNDy neurons significantly reduced the elevated body temperature. 95 Taken together, this series of preclinical experiments emphasises the importance of KNDy neurons in the generation of hot flushes, as well as the promise of targeting these neurons to treat vasomotor symptoms.…”
Section: Manipulating Neurokinin B-signalling To Treat Menopausal Flu...mentioning
confidence: 69%
See 2 more Smart Citations
“…95 In this study, inhibition of kisspeptin neuronal activity by chronic administration of kappa opioid receptor agonists to bilaterally ovariectomised mice with experimentally induced hyperactivity of KNDy neurons significantly reduced the elevated body temperature. 95 Taken together, this series of preclinical experiments emphasises the importance of KNDy neurons in the generation of hot flushes, as well as the promise of targeting these neurons to treat vasomotor symptoms.…”
Section: Manipulating Neurokinin B-signalling To Treat Menopausal Flu...mentioning
confidence: 69%
“…Moreover, a very recent study examined the effects of administration of a peripherally restricted kappa receptor agonist (which can access brain areas including the ARC via the fenestrated capillaries of the median eminence) on vasomotor symptoms 95 . In this study, inhibition of kisspeptin neuronal activity by chronic administration of kappa opioid receptor agonists to bilaterally ovariectomised mice with experimentally induced hyperactivity of KNDy neurons significantly reduced the elevated body temperature 95 . Taken together, this series of preclinical experiments emphasises the importance of KNDy neurons in the generation of hot flushes, as well as the promise of targeting these neurons to treat vasomotor symptoms.…”
Section: Therapeutic Application In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these studies suggest that the opioid signaling component of the KNDy pathway may be involved in PCOS pathophysiology and may be an important therapeutic target. Indeed, a recent preclinical study in PNA mice suggests that the KOR agonist difelikefalin, which does not cross the blood–brain barrier but still has access to regions near the fenestrated capillaries of the median eminence, ameliorates estrous cyclicity in addition to reducing serum testosterone 144 . Such results in an animal model with PCOS‐like features suggest that KOR agonists deserve further study as potential pharmacological agents for PCOS.…”
Section: Aberrant Reproductive Neuroendocrine Activity In Preclinical...mentioning
confidence: 99%
“…In a recent example of this strategy, Navarro and colleagues 70 demonstrated that peripherally restricted KOR agonists reduce the magnitude of LH pulse secretion in pDHT mice, while reducing testosterone levels and restoring cyclicity and ovulation. 70 The development of peripherally restricted drugs may therefore specifically target cells controlling fertility without adversely affecting other brain systems that control cognition, mood and other higher-order functions. This provides a promising avenue for the development of future therapeutic treatments in PCOS.…”
Section: Strategies To Target the Brain In Pcos Patientsmentioning
confidence: 99%